2021
DOI: 10.1108/ilt-07-2020-0283
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shot peening on the wear behavior of Ti(C,N) coating on TA15 alloy prepared by double glow plasma carbonitriding

Abstract: Purpose The purpose of this paper is to prepare Ti(C,N) coatings on TA15 treated and not treated by shot peening using double glow plasma alloying technique. The effect of shot peening on the wear behavior of Ti(C,N) coatings is discussed. Design/methodology/approach The Ti(C,N) coatings were prepared by double glow plasma alloying technique on two different TA15 substrate; one is shot peened and the other is not. Findings Ti(C,N) coating on SP-treated TA15 was thicker and denser, and the grain size was sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…EDS analysis of spots 1 and 2 indicated that the wear trace contains a large amount of Ti, Al, O and a small amount of C, but almost no N. The presence of O atoms in the wear scar region is because of oxidation caused by temperature rise. The reason for the low content of N and C atoms in the wear area is that EDS analysis of N and C elements with lighter atomic mass is only qualitative analysis (Xue et al , 2021). In the comprehensive results, it was found that the wear mechanism of carbide coating on TA15 substrates is abrasive wear and oxidation wear (Cui et al , 2017).…”
Section: Resultsmentioning
confidence: 99%
“…EDS analysis of spots 1 and 2 indicated that the wear trace contains a large amount of Ti, Al, O and a small amount of C, but almost no N. The presence of O atoms in the wear scar region is because of oxidation caused by temperature rise. The reason for the low content of N and C atoms in the wear area is that EDS analysis of N and C elements with lighter atomic mass is only qualitative analysis (Xue et al , 2021). In the comprehensive results, it was found that the wear mechanism of carbide coating on TA15 substrates is abrasive wear and oxidation wear (Cui et al , 2017).…”
Section: Resultsmentioning
confidence: 99%
“…TA15 titanium alloy is a near-alpha type titanium alloy with high Al equivalent, which is strengthened by solid solution of α-stable element Al, and can be used in the production of thin sheets, forgings, profiles, etc. It is often used in the production of engine structural parts or key components, and is also one of the main materials of aircraft body structure, which has important application scenarios in the aviation field [2][3][4] . TA15 titanium alloy is prone to fatigue damage in complex service environment, and the main damage form is fatigue fracture [5] , which affects the safe service of aircraft.…”
Section: Introductionmentioning
confidence: 99%